Religion in The Digital Space: The Potential of Social Media for Religious Conflict Mediation - Muhammad Arifin; Sukapti Sukapti; Ahmad Ridha Mubarak; Arun Panrita Arifin; Sinan Ck Koottilangadi (Al-Albab, 2026)
Religious conflict remains a complex issue worldwide, including in Indonesia. The rise of digital spaces, particularly social media, has not only expanded the religious public sphere but also offered new opportunities for conflict resolution. This article examines the potential of social media as a medium for mediating religious conflicts by highlighting interfaith dialogue, peace-oriented narratives, and the role of religious actors in managing tensions. Employing a qualitative approach grounded in a literature review, the study uses John Paul Lederach’s Conflict Transformation theory as the primary analytical framework to conceptualize digital space as a relational, structural, and narrative environment in which religious conflict is continuously reproduced and potentially transformed. The findings suggest that while social media algorithms tend to amplify hate speech and deepen echo chambers, these same platforms also enable participatory, wide-reaching initiatives for conflict mediation. Thus, digital spaces can be transformed into inclusive arenas for constructive engagement, symbolic rituals, and collaborative practices that foster positive peace and social justice while at the same time facing structural constraints, such as algorithmic polarization, digital inequality, and performative peacebuilding.